Chemoselective synthesis and anti-kinetoplastidal properties of 2,6-diaryl-4H-tetrahydro-thiopyran-4-one S-oxides: their interplay in a cascade of redox reactions from diarylideneacetones - Gendron, Thibault; Lanfranchi, Don A.; Wenzel, Nicole; Kessedjian, Hripsimée; Jannack, Beate; Maes, Louis; Cojean, Sandrine; Müller, Thomas J. J.; Loiseau, Philippe M.; Davioud-Charvet, Elisabeth (Molecules, 2024)
2,6-Diaryl-4H-tetrahydro-thiopyran-4-ones and corresponding sulfoxide and sulfone derivatives were designed to lower the major toxicity of their parent anti-kinetoplatidal diarylideneacetones through a prodrug effect. Novel diastereoselective methodologies were developed and generalized from diarylideneacetones and 2,6-diaryl-4H-tetrahydro-thiopyran-4-ones to allow the introduction of a wide substitution profile and to prepare the related S-oxides. The in vitro biological activity and selectivity of diarylideneacetones, 2,6-diaryl-4H-tetrahydro-thiopyran-4-ones, and their S-sulfoxide and sulfone metabolites were evaluated against Trypanosoma brucei brucei, Trypanosoma cruzi, and various Leishmania species in comparison with their cytotoxicity against human fibroblasts hMRC-5. The data revealed that the sulfides, sulfoxides, and sulfones, in which the Michael acceptor sites are temporarily masked, are less toxic against mammal cells while the anti-trypanosomal potency was maintained against T. b. brucei, T. cruzi, L. infantum, and L. donovani, thus confirming the validity of the prodrug strategy. The mechanism of action is proposed to be due to the involvement of diarylideneacetones in cascades of redox reactions involving the trypanothione system. After Michael addition of the dithiol to the double bonds, resulting in an elongated polymer, the latter—upon S-oxidation, followed by syn-eliminations—fragments, under continuous release of reactive oxygen species and sulfenic/sulfonic species, causing the death of the trypanosomal parasites in the micromolar or submicromolar range with high selectivity indexes.
Online veröffentlicht am 4. April 2024
Gesehen am 18.11.2024